Pseudocapacitive and dual-functional electrochromic Zn batteries - Chen, Jingwei (2022)
The similarity in electrochemical mechanisms in electrochromic and energy storage devices has inspired explorations of dual-functional devices. However, complementary dual-functional devices often neglect charge balance and suffer from unsatisfactory capacity. Here, electrochemically deposited NiO was balanced by Zn anode, constructing an electrochromic Zn battery (EZB) in both aqueous mild (ZnCl2) and alkaline (KOH) electrolytes. With well-adjusted electrochemical deposition condition, nanoporous instead of dense NiO film was obtained, manifesting faster switching for electrochromism and higher capacity for charge storage. In addition, the alkaline EZB outperforms the mild counterpart, due to the formation of larger content of Ni3+ species upon oxidation. The alkaline EZB harvests areal capacity of 20 mAh/m2 at 0.02 mA/cm2 and high-rate performance (17.1 mAh/m2 at 0.2 mA/cm2) for energy storage, while achieving optical contrast of 36%, high transmittance at clear state (>90%), fast switching time (tb = 5.3s, tc = 1.9s), and excellent switching stability (no contrast degradation after 2000 cycles) for electrochromism. A 5∗5 cm2 charged alkaline NiO//Zn EZB can power a timer for more than 30 min, accompanied by a gradual bleaching process, demonstrating the outstanding dual functionalities. This work presents the construction of excellent dual-functional EZB.